A new dimension in exploring stock price movement. (26th January 2023) - Ilyas, Umer; Butt, Matti Ullah; Gulzar, Muhammad; Quddoos, Muhammad Umer
This study unfolds the deficiencies of traditional index base studies and explores the macroeconomic determinants of stock price movement in Pakistan with the aid of panel ARDL model with co-integration and with the objective to provide knowledge platform applicable beyond the geographical boundaries by overcoming the deficiencies of traditional index base studies. Monthly data for the period of 2005 to 2020 were collected for exchange rate, foreign direct investment, interest rate, foreign exchange reserve and exports along with month end share price for analysis. This study captures the impact of these variables first on overall sector and then on each individual firm within same sector to analyse is there any difference in response for both. The results of the study rejected the conventional methods of adopting stock index for decision making as for most cases the overall sector response found different as compared to firms within same sector.